Role of Procalcitonin, qSOFA, and MASCC Score in Predicting Mortality and Intensive Care Unit Admission for Patients with Chemotherapy-Induced Febrile Neutropenia - Doshi, Mrugal; Bhise, Rohan; Mehrotra, Kritika (Indian Journal of Medical and Paediatric Oncology, 2025)
Febrile neutropenia is one of the major complications in patients receiving chemotherapy. In terms of the burden of disease, including mortality, hospital admissions, intensive care unit (ICU) admissions, and financial burden, febrile neutropenia plays a major role in patients receiving chemotherapy.The study aimed to evaluate the role of procalcitonin (PCT), Quick Sequential Organ Failure Assessment score, and the Multinational Association of Supportive Care in Cancer (MASCC) score in predicting mortality and ICU admission.A prospective observational study was performed at two tertiary oncology centers. Forty-seven adult patients diagnosed with chemotherapy-induced febrile neutropenia were enrolled over 12 months. Demographic, clinical, and laboratory data were collected for each patient. Admission risk scores (qSOFA, MASCC, and Clinical Index of Stable Febrile Neutropenia [CISNE]) as well as PCT levels were collected. Statistical analyses were conducted using SPSS v 26 and a p-value <0.05 was considered statistically significant.The majority of the cohort had solid malignancies (n = 30, 63.8%). Among culture-positive cases, 75% were infected with gram-negative organisms, followed by 25% with gram-positive organisms. The low and high risk scores for MASCC were found to be 57.4 and 42.6%, respectively. Respiratory rate, granulocyte colony-stimulating factor, systolic blood pressure, qSOFA, MASCC score, CISNE, oral mucositis, and gastrointestinal tract mucositis were significantly associated with mortality. Patients with PCT >1 ng/mL exhibited higher qSOFA and CISNE scores with p-values of 0.004 and 0.001, respectively, and lower MASCC scores (p = 0.005).PCT, qSOFA score, and MASCC score were effective in predicting mortality in patients with febrile neutropenia.
Keywords: procalcitonin; sepsis; mortality; qSOFA; febrile neutropenia; ICU admission